2016
DOI: 10.1111/1460-6984.12259
|View full text |Cite
|
Sign up to set email alerts
|

Motor‐based treatment with and without ultrasound feedback for residual speech‐sound errors

Abstract: Background There is a need to develop effective interventions and to compare the efficacy of different interventions for children with residual speech sound errors (RSSEs). Rhotics (the r-family of sounds) are frequently in error American English-speaking children with RSSEs and are commonly targeted in treatment. One treatment approach involves the use of ultrasound visual feedback of the tongue. Aims Although prior studies have shown that children with RSSEs acquire rhotics and generalize to untrained word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…A speech-language pathologist (SLP) typically provides cues to help the learner shape his/her output into a closer match for the model. A common approach provides a real-time image of the articulators using technologies such as electromagnetic articulography (e.g., Katz et al, 2010), ultrasound (e.g., Adler-Bock et al, 2007; Preston et al, 2013, 2014, 2016; McAllister Byun et al, 2014b), or electropalatography (e.g., Gibbon et al, 1999). An alternative approach is visual-acoustic biofeedback, in which learners view a dynamic representation of the formants or resonant frequencies of the vocal tract (Shuster et al, 1992, 1995; McAllister Byun and Hitchcock, 2012; McAllister Byun et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…A speech-language pathologist (SLP) typically provides cues to help the learner shape his/her output into a closer match for the model. A common approach provides a real-time image of the articulators using technologies such as electromagnetic articulography (e.g., Katz et al, 2010), ultrasound (e.g., Adler-Bock et al, 2007; Preston et al, 2013, 2014, 2016; McAllister Byun et al, 2014b), or electropalatography (e.g., Gibbon et al, 1999). An alternative approach is visual-acoustic biofeedback, in which learners view a dynamic representation of the formants or resonant frequencies of the vocal tract (Shuster et al, 1992, 1995; McAllister Byun and Hitchcock, 2012; McAllister Byun et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…We plan to enroll a total of 110 children with RSE. Our previous work comparing biofeedback and nonbiofeedback treatment found a median effect size (Cohen's d) of .70 for MBT versus ultrasound treatment [14] and .64 for MBT versus visual-acoustic biofeedback [11]. Because both biofeedback types will be represented in the biofeedback treatment condition in C-RESULTS RCT, we use .67 as our best estimate of the likely effect size of the difference between biofeedback and MBT conditions.…”
Section: Methods and Designmentioning
confidence: 99%
“…A number of recent studies have documented positive responses to biofeedback treatment in individuals who showed minimal response to previous intervention. This is true of both visual-acoustic [10][11][12] and ultrasound [13][14][15][16] types of biofeedback. Many of these studies have used single-case experimental methods to compare gains in biofeedback-enhanced treatment versus traditional forms of intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the average accuracy on words containing /r/ across 11 American English speaking participants ages 10-20 years who were treated for /r/ distortions. The data are from multiple-baseline across-subjects single case designs 13,34 . Some of the participants were treated on other sounds as well, although the figure is restricted to accuracy of /r/ in one word position per participant.…”
Section: Using Real-time Ultrasound Images For Feedback To Remediate mentioning
confidence: 99%